Development of Steam-C Integrated Student Worksheets to Improve Creative Thinking Ability on Flat Side Building Materials - Edy Suprapto; Ika Krisdiana; Davi Apriandi; Fitria Rizqy Yuanawati (STAI Hubbulwathan Duri, 2023)
This study aims to develop and produce the STEAM-C integrated worksheets to improve students' creative thinking skills on the flat-sided building material. Development of student worksheets uses the ADDIE model, namely Analysis, Design, Development, Implementation , and Evaluation . The research was carried out at SMPN 10 Madiun, using 6 students in grade 8D in a limited trial and using grade 8F students as many as 24 students in a field trial. The results of this study are 1) The STEAM-C integrated student worksheets is declared valid with a validity percentage of 81%. 2) The STEAM-C integrated student worksheets is stated to be very practical based on the results of the calculation of the student response questionnaire in a limited trial with a practicality level of 97%, in a field trial with a practicality level of 93%. 3) The STEAM-C integrated student worksheets is declared effective in the high category based on the calculation of the N - Gain value in the limited trial of 86% and in the field trial of 71%. Thus the STEAM-C integrated student worksheets is feasible to be used in improving creative thinking abilities.